Pengaruh Price Earning Ratio (PER) dan Quick Ratio terhadap Harga Saham pada PT Darya-Varia Laboratoria Tbk - Satria Pamungkas; M. Rimawan; Oviriyadin (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This research examines the effect of Price Earning Ratio (PER) and Quick Ratio (QR) on stock prices of PT Darya-Varia Laboratoria Tbk during the 2014–2023 period. The study employs annual financial statements collected from the company’s official website and the Indonesia Stock Exchange. The analysis applies multiple linear regression along with classical assumption tests, t-tests, F-tests, and the coefficient of determination to measure both partial and simultaneous influences of the independent variables on stock prices. The findings are expected to reveal the extent to which PER and QR contribute to explaining stock price fluctuations and to provide useful insights for investors, corporate management, and other stakeholders in making informed investment decisions.